Understanding the role of learning and teaching support materials in enabling learning for all. Issue 4 (4th July 2019) - Milligan, Lizzi O.; Koornhof, Hannchen; Sapire, Ingrid; Tikly, Leon
Abstract: There are many assumptions about the ways in which textbooks and other learning and teaching support materials (LTSM) can contribute to improved learning outcomes in many international contexts. These can focus on ways that they can implement the school curriculum, often in lieu of good pedagogical practice. Drawing on case studies from Rwanda and South Africa, the complexity of the role of LTSM as part of classroom enactment is shown. The discussion suggests that there are enabling factors to this including support for teachers' use of LTSM and the availability of materials to all learners. A framework is presented in which LTSM, teachers and learners can become equal partners in teaching and learning, but only when adequate language and other pedagogical support structures are provided. Conclusions consider the potential impact for LTSM use when it is elevated to a medium that is accessible and useful to both teachers and learners.